2019
DOI: 10.1088/1757-899x/543/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Pyrolysis of Polypropylene Plastic Waste into Liquid Fuel: Reactor Performance Evaluation

Abstract: The amount of plastic waste is growing over years due to the vast applications of plastics in many sectors. Of the various processes that can be used to convert solid waste into fuels, the pyrolysis process has been identified as having significant potential. Pyrolysis thermally degrading long chain polymer molecules into smaller, less complex molecules, through heat and pressure with little or in absence of oxygen. In this study, a 125 dm3 pyrolysis reactor was designed and its performance was evaluated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Pyrolysis is an interesting disposal alternative for plastic wastes, including those from medical use ( Qin et al, 2018 ), without the need for material-based segregation ( Demirbas, 2004 ; Moreira et al, 2017 ). According to the researchers, the high PP content in medical PPE, which including face masks and isolation gowns, could result in substantial yields of liquid and gas fuels, as demonstrated in previous studies with PP wastes ( Ahmad et al, 2015 ; Martynis et al, 2019 ).…”
Section: Future Prospectsmentioning
confidence: 91%
See 1 more Smart Citation
“…Pyrolysis is an interesting disposal alternative for plastic wastes, including those from medical use ( Qin et al, 2018 ), without the need for material-based segregation ( Demirbas, 2004 ; Moreira et al, 2017 ). According to the researchers, the high PP content in medical PPE, which including face masks and isolation gowns, could result in substantial yields of liquid and gas fuels, as demonstrated in previous studies with PP wastes ( Ahmad et al, 2015 ; Martynis et al, 2019 ).…”
Section: Future Prospectsmentioning
confidence: 91%
“… a Ref. – 1 - ( Park et al, 2019 ); 2 - ( Sonawane et al, 2015 ); 3 - ( Sajdak and Muzyka, 2014 ); 4 - ( Das and Tiwari, 2018a ); 5 - ( Williams and Slaney, 2007 ); 6 - ( Aguado et al, 2002 ); 7 - ( Adrados et al, 2012 ); 8 - ( Demirbas, 2004 ); 9 - ( Wong and Broadbelt, 2001 ); 10 - ( Williams and Williams, 1999 ); 11 - ( Ballice and Reimert, 2002 ); 12 - ( Martynis et al, 2019 ); 13 - ( Kusrini et al, 2019 ); 14 - ( Bow and Pujiastuti, 2019 ); 15 - ( Lin and Yen, 2005 ); 16 - ( Ahmad et al, 2015 ); 17 - ( Sakata et al, 1999 ); 18 - ( Norbert Miskolczi et al, 2004 ); 19 - ( FakhrHoseini and Dastanian, 2013 ). …”
Section: Pyrolytic Parametersmentioning
confidence: 99%
“…Pyrolysis requires a simple equipment design, and its impact on the environment is minimal. Furthermore, pyrolysis is an effective alternative to the valorization method of converting plastic waste (i.e., plastics from PPE in general and plastics from protective face masks and clothes in particular) into liquid fuel, thus helping alleviate the current problem of inadequate waste management ( Aragaw and Mekonnen, 2021 , Martynis et al, 2019 , Park et al, 2019 , Su et al, 2021 ). Recently, researchers have produced syngas and C1-2 hydrocarbon from disposable masks by using CO 2 -assisted pyrolysis ( Jung et al, 2021 ).…”
Section: Face Mask Waste Management (Valorization)mentioning
confidence: 99%
“…Due to the usefulness of all the products and their collection for further use, unlike incineration, no product stream is directly open to the environment, which makes it a green process. It is reported by multiple previous studies that oil fraction reaches the maximum among all pyro-products when plastic or synthetic polymeric materials are used as feedstock [30,31]. Operating temperature of pyrolysis plays the key role in the yield of maximum liquid or gas via the pyrolysis process, having a typical range of 623-873K.…”
Section: Pyrolysis: a Promising Resource Resurgence Route For Covid-wastementioning
confidence: 99%
“…Fine-tuning of these factors controls the percentage of aromatics and other desired chemicals in the pyro-oil and its fuel value (calorific value or higher heating value). Over the last decade, numerous research articles investigated and reported effect of several parameters of pyrolysis of different types of polymeric plastics (PP, LDPE, HDPE, PET, and PS) on the production of pyro-oil [30,31,33,39,40]). This will drive the adoption of pyrolysis as an efficient COVID-waste management and recycling method and construction of dedicated pyrolysis plants for the said purpose.…”
Section: Pyrolysis: a Promising Resource Resurgence Route For Covid-wastementioning
confidence: 99%